2014
DOI: 10.1120/jacmp.v15i5.4724
|View full text |Cite
|
Sign up to set email alerts
|

Comparing conformal, arc radiotherapy and helical tomotherapy in craniospinal irradiation planning

Abstract: Currently, radiotherapy treatment plan acceptance is based primarily on dosimetric performance measures. However, use of radiobiological analysis to assess benefit in terms of tumor control and harm in terms of injury to normal tissues can be advantageous. For pediatric craniospinal axis irradiation (CSI) patients, in particular, knowing the technique that will optimize the probabilities of benefit versus injury can lead to better long‐term outcomes. Twenty‐four CSI pediatric patients (median age 10) were retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
2
17
0
2
Order By: Relevance
“…Our dosimetric results were comparable to several dosimetric studies that have investigated highly conformal radiotherapy techniques such as IMRT, HT, or VMAT for CSI planning, most of which found that the use of VMAT, compared to conventional CSI, significantly reduces OAR doses while preserving good target coverage. With a 36 Gy dose and RapidArc technology, Fogliata et al.…”
Section: Discussionsupporting
confidence: 79%
“…Our dosimetric results were comparable to several dosimetric studies that have investigated highly conformal radiotherapy techniques such as IMRT, HT, or VMAT for CSI planning, most of which found that the use of VMAT, compared to conventional CSI, significantly reduces OAR doses while preserving good target coverage. With a 36 Gy dose and RapidArc technology, Fogliata et al.…”
Section: Discussionsupporting
confidence: 79%
“…c .The interval time of surgery and radiotherapy is twelve weeks. 1 .M0 vs M2; 2 .M0 vs M3; 3 .M0 vs M2; 4 .M0 vs M3; 5 .None vs EP; 6 .None vs TMZ; 7 .None vs EP; 8 .None vs TMZ. Survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge,IMRT, volumetric-modulated arc therapy (VMAT), Tomotherapy (TOMO) and other modern radiotherapy technologies are obviously better than 3D-CRT and conventional radiotherapy technologies in terms of dose distribution in the target volume and normal tissue protection [2][3][4].Previous study have shown that 3D-CRT avoiding failures related to radiotherapy uncertainties to some extent, but there are still 1/3 failures statement [5]. Previous study had shown the pattern of failure associated with medulloblastoma patients treated with proton radiation therapy was similar to the pattern of failure in patients treated with photon radiation therapy [6].Howerver, there are few reports about recurrence patterns after radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In craniospinal irradiation the large target volume needs complex treatment planning. With the exception of helical tomotherapy treatments, it entails setting multiple isocenters and matching a large number of fields to obtain satisfactory plans . The field junction area is a critical region, because under‐dosage may compromise tumor control, while over‐dosage may increase the risk of serious radiation‐induced late effects, e.g.…”
Section: Introductionmentioning
confidence: 99%